Creación del plan estratégico y diseño de un sistema de monitoreo basado en el balanced scorecard a una empresa que ofrece servicios de consultoría y auditoría en la ciudad de Guayaquil - Muñiz, Marco (2009)
The Balanced Scorecard is a methodology that integrates and measures the possible generators of values in the companies, giving emphasis to the potential intangible’s asset and its interaction with the rest of the business assets. Nowadays any big, median or small organization, of production or services, has to complete the objectives that gave origin and that justified the reason to be of the same, therefore that the initiative born to realize a thesis that generally consists in the “Creation of a Strategic Plan and Design of a Monitoring System based on the Balanced Scorecard to a Company that Offers consulting and Audit Services in the city of Guayaquil". This process begins with the creation of the strategic plan of the company. This strategy we translated in easy parameters of measuring by means of the creation of gestion indicators to evaluate in efficient way that we planning in a first time, with them the creation of the instruments to capture information that at the same time It will go together with the software that will be able to do a monitoring of the business objectives, all based in the Balanced Scorecard.